Optimizing of Resources Utilization Through Islamic Spiritual Enterpreneurship to Improve The Welfare of Coastal Communities - Rustan Rustan; Andi Arifwangsa Adiningrat; Siti Aisyah (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to determine the efforts of coastal communities in optimizing the utilization of natural resources through Islamic Spiritual Entrepreneurship which is applied to improve the welfare of coastal communities. The urgency of research on the principle of